Does Awareness of Writing Process Improve the Student’s Writing Skills? - Sivakami, Dr.B. (International Journal of Psychosocial Rehabilitation, 2020)
The gap in the competent writing skills expected of students for a few positions in companies, and the writing skills which they possess, in actual, out of the practice in the class assignments given bring to limelight the necessity for following the techniques in writing, and paucity of time for the teachers to impart techniques to students in the class for enhancing their writing skills. The researchers’ quench for finding out the impact of the appropriate techniques to improve the writing skills by creating awareness about the writing process has kindled to carry out the present study. A single group pre and post-test design was followed to find out whether it proves the researchers’ surmise in the failure of following the writing techniques on the part of students. The subsequent analysis employing the paired t test confirmed the actual practice in the class which has been bereft of the knowledge of students about the writing process.